2021
DOI: 10.1038/s41598-021-96109-w
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting SARS-CoV-2 infection in vitro by suppressing its receptor, angiotensin-converting enzyme 2, via aryl-hydrocarbon receptor signal

Abstract: Since understanding molecular mechanisms of SARS-CoV-2 infection is extremely important for developing effective therapies against COVID-19, we focused on the internalization mechanism of SARS-CoV-2 via ACE2. Although cigarette smoke is generally believed to be harmful to the pathogenesis of COVID-19, cigarette smoke extract (CSE) treatments were surprisingly found to suppress the expression of ACE2 in HepG2 cells. We thus tried to clarify the mechanism of CSE effects on expression of ACE2 in mammalian cells. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 40 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…Vero E6 cell lines have also been used in multiple studies of SARS-CoV-2 repurposed antivirals ( Canal et al., 2021 , Leneva et al., 2021 ), protease inhibitors ( Cui and Jia, 2021 ; Han et al., 2021 ) as well as inhibiting peptides ( Kelesidis et al., 2021 ). This cell line model was used in research investigating the indirect inhibition of the ACE-2 receptor as a possible SARS-CoV-2 therapeutic ( Tanimoto et al., 2021 ) along with human polyclonal IgG ( Gilliland et al., 2021 ). Treating SARS-CoV-2 infection with repurposed drugs has been an area of intense research due to the speed at which these therapeutics can be approved and implemented into the clinical setting.…”
Section: In Vitro Models Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Vero E6 cell lines have also been used in multiple studies of SARS-CoV-2 repurposed antivirals ( Canal et al., 2021 , Leneva et al., 2021 ), protease inhibitors ( Cui and Jia, 2021 ; Han et al., 2021 ) as well as inhibiting peptides ( Kelesidis et al., 2021 ). This cell line model was used in research investigating the indirect inhibition of the ACE-2 receptor as a possible SARS-CoV-2 therapeutic ( Tanimoto et al., 2021 ) along with human polyclonal IgG ( Gilliland et al., 2021 ). Treating SARS-CoV-2 infection with repurposed drugs has been an area of intense research due to the speed at which these therapeutics can be approved and implemented into the clinical setting.…”
Section: In Vitro Models Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…However, it must be considered that these data are preliminary and that the anti-androgenic effect of FICZ, which also reverberates on DHT and Prostate-Specific Antigen (PSA) levels, could be a serious side-effect of a hypothetical FICZ-based anti-COVID-19 therapy. An interesting discrepancy concerning AhR involvement in the management of SARS-CoV-2 infection comes from Tanimoto’s study [ 31 ] that recently highlighted an inverse correlation between ACE-2 expression and AHR activation in non-respiratory mammalian cell lines using its agonists FICZ, omeprazole (OMP) and Cigarette Smoke Extract (CSE). According to Tanimoto’s data, the more the AHR pathway is activated, the less ACE-2 is expressed, and consequently, the viral load decreases.…”
Section: Ahr Modulates Ace-2 and B 0 At1mentioning
confidence: 99%
“…Another explanation was provided by Tanimoto et al, (2021), who reported that cigarette smoke extract (CSE) treatments were, surprisingly, found to suppress the expression of ACE2 in HepG2 cells [ 22 ]. Interestingly, the effect of smoking on the Antibody titer after vaccination is inverted.…”
Section: Discussionmentioning
confidence: 99%